2013
DOI: 10.1007/s00276-013-1077-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the infraorbital groove, canal, and foramen on three-dimensional reconstruction of computed tomography scans

Abstract: These results provide detailed knowledge of the anatomical characteristics and clinical importance of the IOF. Such knowledge is of paramount importance for surgeons when performing maxillofacial surgery and regional block anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
2
33
3
6
Order By: Relevance
“…Hence, headshaking has been suggested to be due to neuropathic pain. There is a long‐standing comparison between idiopathic headshaking and trigeminal neuralgia, a neuropathic pain syndrome in humans; compression of the trigeminal nerve as seen on MRI in human patients is a commonly stated cause of trigeminal neuritis …”
Section: Introductionmentioning
confidence: 99%
“…Hence, headshaking has been suggested to be due to neuropathic pain. There is a long‐standing comparison between idiopathic headshaking and trigeminal neuralgia, a neuropathic pain syndrome in humans; compression of the trigeminal nerve as seen on MRI in human patients is a commonly stated cause of trigeminal neuritis …”
Section: Introductionmentioning
confidence: 99%
“…The first one involves experimental procedures carried out on cadaveric and dry skulls [3][4][5][6][7][8][9][10][11][12]. The second one involves the evaluation of cranial structures by MDCT [13]. The findings of the previous studies that used cadaveric skulls and dry skulls showed the variability of size and position of IOF.…”
Section: Discussionmentioning
confidence: 97%
“…Various anatomical studies have been conducted with the aim to describe anatomical variations of the exit point of the infraorbital nerve and vessels from the orbit [6][7][8][9][10][11][12][13]. For a number of years, the research on the morphometry of the IOF has been realized on cadaveric or dry skulls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear understanding of facial anatomy is critical to avoid a catastrophic complication, such as inadvertent vessel cannulation. The principal facial foramina and large periocular vessels can be accurately localized using the patient’s pupil as a global positioning system: the supraorbital vessels are aligned with the medial iris limbus, and the infraorbital vessels fall between the pupil and the medial iris 3234 (Fig. 4).…”
Section: Soft-tissue Fillers: Hyaluronic Acid (Restylane Juvederm Amentioning
confidence: 99%